ANALISIS IMPLEMENTASI PERAN ACCOUNTING CONCEPTUAL FRAMEWORK DALAM KAJIAN DISIPLIN ILMU AKUNTANSI - Vita Tri Indriani; Khairun Nisa; Nailis Syafa Kamila; Gunawan Aji (CV. KAMPUS AKADEMIK PUBLISING, 2024)
A conceptual framework is a system that links the objectives and principles that form the foundation of accounting, ultimately leading to the development of consistent standards to describe the essence, functions and limitations of accounting and financial reporting. Conceptual frameworks play an important role in the advancement of new accounting standards and revisions of previously implemented accounting standards. In situations where accountants face new accounting problems without established standards, a conceptual framework serves as a valuable tool for analyzing and resolving these problems. This research will discuss further the role, obstacles and implications of the accounting conceptual framework. This research uses a qualitative approach with literature analysis. Data was collected from various sources including relevant books, articles and journals. The results of this research show that the role of the conceptual framework is as a guide to preparing financial reports, understanding basic accounting concepts, helping to handle controversial scenarios in the field of accounting, comparing financial reports. The obstacles are limited understanding of accountants, limitations in the field of technology, and limitations in policy standards. The implications are increasing the relevance of accounting information, utilizing information technology, strengthening corporate governance.